Palladium‐Catalyzed Cascade Cyclization/Alkylation of Oxime Ethers: Assembly of 4‐Alkylisoxazoles by "Chain‐Walking" Strategy. Issue 21 (7th September 2022) - Lai, Yin‐Long; Yan, Shao‐Xi; Zhang, Sheng‐Ling; Huang, Yu‐Hong; Hu, Ru‐Xin; Chen, Yang‐Chong; Luo, Jian‐Min; Li, Jianxiao
Abstract: A reliable and efficient palladium‐catalyzed cascade cyclization/alkylation of oxime ethers with unactivated alkenes is described, affording a whole variety of structurally diverse isoxazole derivatives in moderate to good yields with excellent functional group compatibility. Ionic liquid [Aeim]Br not only acts as an environmentally friendly solvent but also acts as an accelerating agent to provide excess bromine source to eliminate bromomethane from oxime ethers. More importantly, the use of "chain‐walking" strategy provides a novel methodology in organic synthesis to rapid generation of molecular complexity from readily available starting materials. Abstract : "Chain‐Walking" alkylation : A reliable and efficient palladium‐catalyzed cascade cyclization/alkylation of oxime ethers with unactivated alkenes is described, affording a whole variety of structurally diverse isoxazole derivatives in moderate to good yields with excellent functional group compatibility.